2005
DOI: 10.1093/bioinformatics/bti796
|View full text |Cite
|
Sign up to set email alerts
|

Gene sequence signatures revealed by mining the UniGene affiliation network

Abstract: Our results show that most NETs resemble intergenic sequences, casting doubts on the quality of such UniGene clusters. However, we also noted that a fraction of NETs resemble PETs in terms of dinucleotide frequencies and other features. Such NETs may have fewer quality problems. This work may be helpful in the studies of non-coding RNAs and in the validation of gene sequence databases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Given that 10 to 20% of EST sequences in UniGene were annotated in the wrong direction [46], reliable in silico screenings must be based on stringent parameters which could underestimate or exclude some genuine antisense transcripts. Nevertheless, we proceeded to experimentally validate our bioinformatics results by performing 5′ RACE experiments on total RNA isolated from the MA-10 Leydig tumor cell line.…”
Section: Resultsmentioning
confidence: 99%
“…Given that 10 to 20% of EST sequences in UniGene were annotated in the wrong direction [46], reliable in silico screenings must be based on stringent parameters which could underestimate or exclude some genuine antisense transcripts. Nevertheless, we proceeded to experimentally validate our bioinformatics results by performing 5′ RACE experiments on total RNA isolated from the MA-10 Leydig tumor cell line.…”
Section: Resultsmentioning
confidence: 99%
“…The ontology term enrichment problem is not restricted to differential gene expression analysis or to microarray derived data. The current models, including the one implemented in BayGO, are capable of analysing the enrichment relative to other dichotomous properties such as "belonging to a particular gene cluster" vs. "not belonging", in clustering analysis [ 24 ]; "it is expressed (ON)" vs. "it is not expressed (OFF)", in gene transcription analysis; "narrowly expressed transcripts" vs. "prevalently expressed transcripts" [ 36 ]; and so on.…”
Section: Resultsmentioning
confidence: 99%
“…In summary, while many recent scans of positive selection have resulted in extensive lists of candidate regions (Kelley et al, 2006; Voight et al, 2006; Wang et al, 2006; Zhang et al, 2006; Kimura et al, 2007; Sabeti et al, 2007; Tang et al, 2007), very little follow-up analysis has been reported. Here, we have focused on a region of chromosome 2p13 that contains three independent substrates of recent positive selection, and we have shown that additional clusters of independent selective events likely exist in the human genome.…”
Section: Discussionmentioning
confidence: 99%